Identifikasi dan Karakterisasi Jamur Penyebab Penyakit Busuk Buah pada Jambu Biji (Psidium Guajava) - Luvyta Sary Siahaan; Ade Adriadi; Ahmad Sazali (Lembaga Pengembangan Kinerja Dosen, 2026)
Fruit rot disease is one of the main obstacles in the cultivation of guava (Psidium guajava) because it directly reduces the quality and selling value of the harvest. This research aims to identify and characterize the fungus that causes fruit rot disease in guava. The research was carried out by observing disease symptoms in the field, isolating the pathogen from infected fruit, as well as macroscopic and microscopic characterization of the fungus using Potato Dextrose Agar (PDA) media. The results of the research show that the initial symptoms are blackish brown spots on the surface of the fruit which develop into sunken lesions and spread to cause the fruit to dry out. The fungal isolate has white colonies with a flower-like pattern and forms black aservuli. Microscopic observation shows that the conidia are fusiform, insulated, with darker pigmented middle cells and have a transparent appendix. Based on these morphological characters, the fungus that causes fruit rot disease in guava is thought to belong to the genus Pestalotiopsis sp. Further research is needed through molecular approaches, such as PCR or DNA sequencing, as well as pathogenicity tests to strengthen and confirm the role of this fungus as the main cause of fruit rot disease.